Diurnal variation of Upper Air Temperatures over India - RANGARAJAN, S.; SIKKA, D. R. (MAUSAM, 1963)
A statistical study of the diurnal variation of upper air temperatures over India is made utilising radiosonde data of four stations for four standard hours of the day and covering four representative months. A marked difference in the pattern of diurnal variation is found between a continental station like New Delhi and the three coastal stations Bombay, Calcutta and Madras. Significant diurnal variations are found over New Delhi only upto 1 to 3 km depending on the season, the mean daily range being about 1 to 2° C in most cases. On the other hand, diurnal variations at the coastal stations extend higher upto 4-6 km, the amplitudes being of the same order. Apparent diurnal variations found at still higher levels are probably due to inadequacy of radiation corrections. Nocturnal cooling of the atmosphere between 600 and 400-mb levels is found to be in the range of 0.1 to 0.15{ per.